Occurrence, fate, and risk assessment of antibiotics in typical pharmaceutical manufactories and receiving water bodies from different regions. - Yuanfei Liu; Dan Cai; Xin Li; Qingyao Wu; Ping Ding; Liangchen Shen; Jian Yang; Guocheng Hu; Jinhua Wu; Lijuan Zhang (PLoS ONE, 2023)
This study aimed to investigate the presence and persistence of antibiotics in wastewater of four typical pharmaceutical manufactories in China and receiving water bodies and suggest the removal of antibiotics by the wastewater treatment process. It also evaluated the environmental impact of antibiotic residues through wastewater discharge into receiving water bodies. The results indicated that thirteen antibiotics were detected in wastewater samples with concentrations ranging from 57.03 to 726.79 ng/L. Fluoroquinolones and macrolides were the most abundant antibiotic classes found in wastewater samples, accounting for 42.5% and 38.7% of total antibiotic concentrations, respectively, followed by sulfonamides (16.4%) and tetracyclines (2.4%). Erythromycin-H2O, lincomycin, ofloxacin, and trimethoprim were the most frequently detected antibiotics; among these antibiotics, the concentration of ofloxacin was the highest in most wastewater samples. No significant difference was found in different treatment processes used to remove antibiotics in wastewater samples. More than 50% of antibiotics were not completely removed with a removal efficiency of less than 70%. The concentration of detected antibiotics in the receiving water bodies was an order of magnitude lower than that in the wastewater sample due to dilution. An environmental risk assessment showed that lincomycin and ofloxacin could pose a high risk at the concentrations detected in effluents and a medium risk in their receiving water bodies, highlighting a potential hazard to the health of the aquatic ecosystem. Overall, The investigation was aimed to determine and monitor the concentration of selected antibiotics in 4 typical PMFs and their receiving water bodies, and to study the removal of these substances in PMFs. This study will provide significant data and findings for future studies on antibiotics-related pollution control and management in water bodies.